Virtual Tour Menggunakan Metode Gambar Panorama Sebagai Media Pengenalan Lingkungan Sekolah - Indra Maulana (Media Aplikom, 2022)
Virtual Reality is one of the applications of multimedia technology which has the advantage of describing an object where the visualization displayed can be seen from all angles, because it has 3 visual dimensions so that users can interact with an environment simulated by a computer. With the advantages of this technology, there are many ideas to be applied in various ways, such as for example to use this technology as a tool for recognition of an environment without having to bother moving or going to the original place. The government's advice to stay at home and physical and social distancing must be followed by changing the face-to-face learning model to online, this also affects the school promotion process which is also carried out online which causes prospective new students to be less familiar with their new school. This virtual reality tour that was built in this final project uses 3dvista as its implementation. Judging from the results of the tester's questionnaire, the ease of using the website gets a value of 3.75 which shows that users are still comfortable and easy to use the website. Then get a suitability value of 4.75 which means the user's website is in accordance with the existing conditions. And this virtual tour is very interesting because it gets an average of 5 which is in the "very good" category, meaning that the menu on this virtual reality tour is very interesting for users